Abiyoyo returns - Seeger, Pete 1919-; Jacobs, Paul DuBois; Hays, Michael 1956- . (New York Aladdin Books, 2001)
Based on a South African tale, this story tells what happens when a giant who had been banished from a town by a magician thirty years earlier is called back to save the town from flooding.
Keywords: Folklore -- South Africa; Magicians -- Folklore; Giants -- Folklore